UTILIZATION OF A FOUR-TIER DIAGNOSTIC TEST IN UNCOVERING MISCONCEPTIONS ON ATOMIC AND MOLECULAR CONCEPTS - Sukaria, M.Ikhsan (MACCA : Science-Edu Journal, 2024)
This study aims to analyze the misconceptions experienced by students using a four-tier diagnostic instrument. This study used a qualitative descriptive approach to map the different types of misconceptions on the concept of ions. The main instrument used is a four-tier diagnostic test, which consists of four tiers: the main question (first tier), the student's level of confidence in answering (second tier), the reason for choosing the answer in the first tier (third tier), and the confidence in the answer of the reason (fourth tier). The test questions are presented using multiple representations, including macroscopic, submicroscopic, and symbolic. The results of validation by experts showed that the instrument was valid, with a reliability of 0.6. The study involved junior high school grade IX students who had learned the concepts of atoms, molecules, and ions. The research findings revealed some major misconceptions related to the concept of atoms such as the atomic nucleus is neutral, atoms are the constituent particles of matter that cannot be subdivided, each atom has a certain color, mass number shows the number of electrons, protons, and neutrons, isotopes are atoms with the same mass number, mass number shows the number of electrons, protons, and neutrons, the number of neutrons is equal to the number of electrons, isotopes are elements with different atomic numbers, atomic size depends on the number of electrons. While for the concept of molecules misconceptions that were successfully identified, molecules change shape with phase changes, the temperature of the substance affects the properties of molecules, atoms and molecules are synonymous terms, compounds consist of several types of molecules The results of this study provide deep insight into conceptual errors that need to be addressed to improve student understanding